Phrasal schemes with the base component-preposition in the Russian language (Proceedings of Southern Federal University. Philology, 2016)
Akbaeva Olga Viktorovna – post-graduate student of language theory and Russian language dpt. Institute of philology, journalism and crosscultural communication. Southern Federal University. This article focuses on parametization of phrasal and syntactic schemes of modern Russian language with the base component-preposition: «На то и + N1! и «N1 + не в + N4». These schemes relate to the construction of a class of syntactic phraseological units and form the core of expressive syntax of the Russian language. They have obligatory and optional components. Phrasal schemes with base component-preposition have integrated and differentiated properties. Phrasal schemes are polysemic, derivative and possess phraseological signs of reproducibility, structural and semantic integrity and stability, idiomatic, colloquial expressivity. Implication of these phrasal schemes in colloquial speech increases the efficiency of the communication process and allows the speaker to realize a variety of authorial intention.Key words: syntax phraseology, phrasal and syntactic scheme, phrasal scheme, phraseological subsystem, sustainability, idiomaticity, expressiveness, Russian language.